Establishing the reliability of a novel battery of range of motion tests to enable evidence-based classification in Para Swimming - Nicholson, V. P.; Spathis, J. G.; Hogarth, L. W.; Connick, M. J.; Beckman, E. M.; Tweedy, S. M.; Payton, C. J.; Burkett, B. J. (Physical Therapy in Sport, 2018)
Objectives: To evaluate the reliability of swimming-specific range of movement tests developed in order to permit evidenced-based classification in the sport of para swimming. Design: Test-retest intra- and inter-examiner reliability. Setting: International Swimming training camps and university exercise science departments. Participants: 42 non-disabled participants (mean age 23.2 years) and 24 Para swimmers (mean age 28.5 years). Main outcome measures: Intra- and inter-examiner reliability of a battery of novel active range of motion tests. Results: Good to excellent intra-examiner reliability was found for the majority (32/34) of tests in non-disabled participants (ICC=0.85-0.98). SEM values ranged from 1.18° to 6.11°. Similarly, good to excellent inter-examiner reliability was found for the majority (35/42) of tests in non-disabled participants (ICC=0.85-0.98). SEM values range from 0.73° to 6.52°. Para swimmers exhibited significantly reduced range of motion compared to non-disabled participants. Conclusions: The large majority of ROM tests included in this novel battery were reliable both within and between examiners in non-disabled participants. The tests were found to differentiate between non-disabled participants and Paraswimmers with hypertonia or impaired muscle power.